L2 speakers decompose morphologically complex verbs: fMRI evidence from priming of transparent derived verbs - De Grauwe, Sophie; Lemhöfer, Kristin; Willems, Roel M.; Schriefers, Herbert (Frontiers in Human Neuroscience, 2014)
In this functional magnetic resonance imaging (fMRI) long-lag priming study, we investigated the processing of Dutch semantically transparent, derived prefix verbs. In such words, the meaning of the word as a whole can be deduced from the meanings of its parts, e.g., wegleggen “put aside.” Many behavioral and some fMRI studies suggest that native (L1) speakers decompose transparent derived words. The brain region usually implicated in morphological decomposition is the left inferior frontal gyrus (LIFG). In non-native (L2) speakers, the processing of transparent derived words has hardly been investigated, especially in fMRI studies, and results are contradictory: some studies find more reliance on holistic (i.e., non-decompositional) processing by L2 speakers; some find no difference between L1 and L2 speakers. In this study, we wanted to find out whether Dutch transparent derived prefix verbs are decomposed or processed holistically by German L2 speakers of Dutch. Half of the derived verbs (e.g., omvallen “fall down”) were preceded by their stem (e.g., vallen “fall”) with a lag of 4–6 words (“primed”); the other half (e.g., inslapen “fall asleep”) were not (“unprimed”). L1 and L2 speakers of Dutch made lexical decisions on these visually presented verbs. Both region of interest analyses and whole-brain analyses showed that there was a significant repetition suppression effect for primed compared to unprimed derived verbs in the LIFG. This was true both for the analyses over L2 speakers only and for the analyses over the two language groups together. The latter did not reveal any interaction with language group (L1 vs. L2) in the LIFG. Thus, L2 speakers show a clear priming effect in the LIFG, an area that has been associated with morphological decomposition. Our findings are consistent with the idea that L2 speakers engage in decomposition of transparent derived verbs rather than processing them holistically.